Outcomes of Patients with a Mechanical Heart Valve and Poor Anticoagulation Control on Warfarin - Johansson, Isabelle; Benz, Alexander P.; Kovalova, Tanya; Balasubramanian, Kumar; Fukakusa, Bianca; Lynn, Matthew J.; Nair, Nikhil; Sikder, Omaike; Patel, Kashyap; Gayathri, Sai; Robinson, Marlene; Hardy, Colin; Tyrwhitt, Jessica; Schulman, Sam; Eikelboom, John W.; Connolly, Stuart J. (Thrombosis and Haemostasis, 2023)
Background Patients with a mechanical heart valve (MHV) require oral anticoagulation. Poor anticoagulation control is thought to be associated with adverse outcomes, but data are limited.Objective To assess the risks of clinical outcomes in patients with a MHV and poor anticoagulation control on warfarin.Methods We conducted a retrospective study of consecutive patients undergoing MHV implantation at a tertiary care center (2010–2019). Primary outcome was a composite of ischemic stroke, systemic embolism, or prosthetic valve thrombosis. Major bleeding and death were key secondary outcomes. We constructed multivariable regression models to assess the association between time in therapeutic range (TTR) on warfarin beyond 90 days after surgery with outcomes.Results We included 671 patients with a MHV (80.6% in aortic, 14.6% in mitral position; mean age 61 years, 30.3% female). Median follow-up was 4.9 years, mean TTR was 62.5% (14.5% TTR <40%, 24.6% TTR 40–60%, and 61.0% TTR >60%). Overall rates of the primary outcome, major bleeding, and death were 0.73, 1.41, and 1.44 per 100 patient-years. Corresponding rates for patients with TTR <40% were 1.31, 2.77, and 3.22 per 100 patient-years. In adjusted analyses, every 10% decrement in TTR was associated with a 31% increase in hazard for the primary outcome (hazard ratio [HR]: 1.31, 95% confidence interval [CI]: 1.13–1.52), 34% increase in major bleeding (HR: 1.34, 95% CI: 1.17–1.52), and 32% increase in death (HR: 1.32, 95% CI: 1.11–1.57).Conclusion In contemporary patients with a MHV, poor anticoagulation control on warfarin was associated with increased risks of thrombotic events, bleeding, and death.
Keywords: mechanical heart valve; outcomes; stroke; TTR; VKA